The Relationship between Mean Arterial Pressure and Obesity with Sleep Quality - Arum, Dyah Ayu Sekar; Setiawan, Iwan; Fithriyah, Saidatul; Basuki, Sri Wahyu (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study is to identify the relationship between mean arterial pressure and obesity with sleep quality. Methodology: This study is an analytical observational study with a cross-sectional approach. Sampling method was simple random sampling and the sample selected was 171 respondents. Data was collected from medical record data of POSKESTREN SMA Boarding School Surakarta and Pittsburgh Sleep Quality Index (PSQI) questionnaire. Results: Fisher test analysis result showed no significant relationship between mean arterial pressure and sleep quality (p=0.116). Chi-square test analysis showed significant relationship between obesity and sleep quality (p=0.0015). Applications/Originality/Value: This study showed the information of relationship between mean arterial pressure, obesity, and sleep quality. This study found that there was no significant relationship between mean arterial pressure and sleep quality. A significant relationship between obesity and sleep quality was found.